2012
DOI: 10.1007/s11430-011-4349-0
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal characteristics of spring phenophase changes of Fraxinus chinensis in China from 1952 to 2007

Abstract: We selected widely distributed and well observed plant species Fraxinus chinensis to study the formation mechanism of geographical distribution of the plant phenophase changes and revealed their spatiotemporal dynamics in China. Based on the first leaf date (FLD) data at 12 sites derived from Chinese Phenological Observation Network (CPON) and related meteorological data, we developed and validated the process-based model of FLD for Fraxinus chinensis. After reconstructing data series of FLD for Fraxinus chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(51 reference statements)
4
8
0
Order By: Relevance
“…For example, over the past 57 years, the advance of peony FFD in Luoyang, Heze, Beijing, and Xi'an was respectively −1.2, −1.6, −1.8, and −1.4 days/decade. Another phenological result from [34] was close to this study: trends of the first leaf date (FLD) for Chinese ash trees (Fraxinus chinensis Roxb.) over the period 1952-2007 were nearly −1.1 days/decade in Henan, −2.0 days/decade in Beijing and Shandong, and −1.4 days/decade in Shaanxi.…”
Section: The Consistency Of Regional Phenological Trendssupporting
confidence: 83%
“…For example, over the past 57 years, the advance of peony FFD in Luoyang, Heze, Beijing, and Xi'an was respectively −1.2, −1.6, −1.8, and −1.4 days/decade. Another phenological result from [34] was close to this study: trends of the first leaf date (FLD) for Chinese ash trees (Fraxinus chinensis Roxb.) over the period 1952-2007 were nearly −1.1 days/decade in Henan, −2.0 days/decade in Beijing and Shandong, and −1.4 days/decade in Shaanxi.…”
Section: The Consistency Of Regional Phenological Trendssupporting
confidence: 83%
“…() reported that changes in precipitation can significantly influence the spring phenology in a semi–arid region of temperate China. Our results, however, are different from model simulations or observed species‐level phonological dynamics in the humid part of China (Bai et al ., ; Ge et al ., ; Wang et al ., ), precipitation has been found to exert little effect on spring phenophases (e.g. first flowering date and first leaf date).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a piecewise linear regression algorithm with one turning point (TP) (Eqn. ) was applied to the BGS series for each pixel from 1982 to 2006 to detect the potential TP at which the BGS trend changed (Wang et al ., ). Before applying the piecewise linear regression, the annual value of the BGS was smoothed using a 3‐year moving average to remove statistical uncertainties caused by the first and last values and individual outliers in the time series.…”
Section: Methodsmentioning
confidence: 97%
“…In China, an increasing number of studies have reported on a latetwentieth century lengthening of growing season as evidenced in satellite data (Piao et al 2006), phenological (Wang et al 2012) and meteorological observations (Xu and Ren 2004;Liu et al 2010;Song et al 2010;Yang et al 2013). The thermal growing season defined based on long time meteorological observations are often used taking advantage of fine spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%